Incidencia de la actividad lúdica como estrategia metodológica para el desarrollo del pensamiento lógico matemático en los niños y niñas del Centro de Educación Inicial María Franco de Carrillo y primer año de la Escuela de Educación Básica Galo Plaza Lasso de la ciudad de Machala periodo 2012-2013. - Ojeda Carpio, Betty Esperanza (2013)
One of the purposes of Initial and Preschool Education, is to look at the boy and girl to develop their capabilities, with a view to study the development of mathematical logical thinking, as the center of formation of his personality, and early childhood education is Parvularia space where a planned education develops skills of infants. This research was conducted at the centers of Initial and Basic Franco Maria Carrillo and Galo Plaza Lasso in the city of Machala, Education for which, the following hypothesis is proposed: The incidence of play activities as a methodological strategy the development of mathematical logical thinking, have had greater significance, on the grounds that teachers do not give a true application of the same. To verify its validity was performed: a literature review, surveys was applied to teachers and observation forms to children. Research instruments that were used to develop the statistical tables and charts as a result we have the following general conclusion: The impact of recreational activities as a methodological strategy for the development of mathematical logical thinking in children have a level of efficient development of thought mathematical logic, lack of renovation and playful enough to implement in the classroom resources. The performance with children due to the lack of implementation of leisure for the development of mathematical calculation does not allow them to have an active participation in the classroom and in the fulfillment of the tasks activities. In deriving the hypothetical approaches as affirmative, it has set the development of a methodological guide for promoting implementation of recreational activities and make the child permanently develops creativity.